2019
DOI: 10.1097/sla.0000000000002319
|View full text |Cite
|
Sign up to set email alerts
|

RAS Mutation Clinical Risk Score to Predict Survival After Resection of Colorectal Liver Metastases

Abstract: Modifying the t-CS by replacing disease-free interval, number of metastases, and CEA level with RAS mutation status produced an m-CS that outperformed the t-CS. The m-CS is therefore a simple validated tool that predicts survival after resection of CLM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
151
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(153 citation statements)
references
References 51 publications
0
151
2
Order By: Relevance
“…Results of multigene panel testing have revealed that cooperation between double mutations plays a critical role in determining patient outcomes. Patient selection for CLM resection should include molecular profiling in addition to traditional prognostic factors 56 . Systemic and surgical therapies may be tailored by individual patients' tumour biology to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of multigene panel testing have revealed that cooperation between double mutations plays a critical role in determining patient outcomes. Patient selection for CLM resection should include molecular profiling in addition to traditional prognostic factors 56 . Systemic and surgical therapies may be tailored by individual patients' tumour biology to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0⋅050, †P ≤ 0⋅001 (χ 2 test) from either the primary tumour or liver metastases, which have over 90 per cent concordance in RAS mutational status 55 . Preoperative knowledge of RAS mutational status can be combined with clinical information regarding node status of the primary tumour and size of the largest liver metastasis, allowing prediction of the prognosis of patients undergoing resection with a preoperative score 56 . Knowledge of RAS mutations can guide decision-making in the operating room and interventional radiology suite.…”
Section: Rasmentioning
confidence: 99%
“…The well established predictors of poor outcome include node‐positive primary cancer, disease‐free interval shorter than 12 months, more than one tumour, tumour size larger than 5 cm, carcinoembryonic antigen (CEA) level exceeding 200 ng/ml, bilobar liver involvement and presence of extrahepatic disease (EHD). Recently, new parameters have also been found to improve the accuracy of current prognostic systems, such as KRAS mutation status, histological growth pattern and the response to preoperative chemotherapy. However, more effective and applicable prognostic factors are still needed to build the optimal preoperative prediction system.…”
Section: Introductionmentioning
confidence: 99%
“…A similar score was constructed by the MD Anderson group. This time, one point was assigned to each of the following factors: RAS mutation, positive primary tumor lymph node status, and a diameter of the largest liver metastasis more than 50 mm . The same group reported in a different study on a relatively different set of factors that, according to the authors, when combined with a KRAS‐mutated tumor should be used to preclude surgery for CRLM.…”
Section: Resultsmentioning
confidence: 99%
“…This time, one point was assigned to each of the following factors: RAS mutation, positive primary tumor lymph node status, and a diameter of the largest liver metastasis more than 50 mm. 36 The same group reported in a different study on a relatively different set of factors that, according to the authors, when combined with a KRAS-mutated tumor should be used to preclude surgery for CRLM. Specifically, patients with a KRAS mutant tumor, a node-positive primary, hepatic metastases more than 3 cm, and more than 7 cycles of preoperative chemotherapy had such poor survival that the authors would advise against surgery.…”
Section: Kras Alone Vs Genetic Risk Score Systems For Surgical Selementioning
confidence: 99%